Meeting decarbonization targets: Techno-economic insights from the Italian scenario - Massimo Beccarello; Giacomo Di Foggia (DeCarbon, 2023)
The European plan for a green transition includes the Fit for 55 package, designed to pave the way for climate neutrality. Despite its significant implications for cleaner technologies, it potentially correlates with high investment requirements, necessitating the pursuit of cost-effective environmental policies. Starting from the reference scenario previously envisaged in the Energy and Climate Plan, socioeconomic and environmental impacts are assessed using mixed methods. It is estimated that exteuro1120 bn in investments are needed to meet decarbonization targets, while the total impact on public finance revenues to 2030 is projected at exteuro529 bn. Additionally, the avoided costs of emissions amount to exteuro36 bn, while those from energy savings are expected to reach exteuro30 bn. This paper adds value by contributing to the literature on European climate policies, offering an in-depth appraisal of implications that integrates technoeconomic and environmental perspectives. Furthermore, it informs policymakers' public spending decisions for decarbonization
Keywords: Q5; L5; 330; Energy economics; energy efficiency; Decarbonization; Energy policy